Calculating the water Ration of the climatic bulb crop in Diyala Governorate - Mozan, Abeer Adnan; Ahmed, Sawsan Kamal (Al-Adab Journal, 2021)
The water ration of the harvest of beans in Diyala governorate was calculated based on the climatic data of the Khanaqin station for the period (1988-2017). The ( Monteith - Penman) equation was used for the Food and Agriculture Organization to calculate the possible evaporatio / transpiration, which is the basis for calculating the water ration of agricultural crops to calculate the regulation and reached the rating Aqueous (21, 48.9, 30, 32.9, 76.5, 153,5 and 2,3) mm, respectively. In the season of planting the legume crop, which extends from the month of (October) to the month of (April), and it was found that the amount of rain fall is low and it is not sufficient to rely on it to meet the water needs to irrigate the crop of leftovers in the months of the agricultural season, And the simple correlation analysis (Pearson coefficient) is the presence of a strong and positive correlation between the water index of the yield of peas and the climatic elements (solar brightness,wind speed, and the amount of evaporation/ transpiration) a medium correlation ,while the minimum temperature has a negative correlation. As for the multiple regression analysis, there is a positive relationship between the water ration of the bean crop and the independent changes (maximum temperatures, wind speed and solar brightness), as the amount of the water ration increases with the higher the values ​​of these variables above, and the amount of the water ration decreases with the lower the values ​​of these variables above, and the existence of a negative relationship between the water rationing The variables are the amount of rain, and as the amount of rain rises, the amount of water rating for the harvest of legumes decreases and vice versa, and the multiple regression coefficient if it reaches (94%) of the fluctuations that affect the amount of the water rating of the remnant transformer in the study area due to the independent variables. Count it if it reaches (6%).